Death of a toy soldier : a vintage toyshop mystery - Early, Barbara (Early, Barbara Vintage toyshop mystery, 2016)
"Liz McCall grew up in a playful winter wonderland, but it was never her dream to settle in her small, albeit charming, hometown. When her father sinks his entire police pension into a vintage toy shop, however, someone needs to help him turn his dreams into reality--and keep him from sneaking out of retirement and off to patrol the not-so-mean streets of East Aurora, NY. The mood goes from nice to naughty when a nervous man, who was trying to have his antique toys appraised, is later found murdered in the shop."--Publisher description